2016
DOI: 10.1016/j.eneco.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting crude oil price volatility and value-at-risk: Evidence from historical and recent data

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
58
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 100 publications
(61 citation statements)
references
References 43 publications
2
58
1
Order By: Relevance
“…Naturally, accurate prediction of oil market movements is of importance to academics, investors and policymakers alike. Understandably, there exists a large literature (see Baumeister, ; Lux et al , ; Degiannakis and Filis, ,; Gupta and Wohar, for detailed reviews) aiming to predict oil price movements using various types of econometric methodologies (univariate and multivariate; linear and non‐linear), and predictors (macroeconomic, financial, behavioural, institutional).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Naturally, accurate prediction of oil market movements is of importance to academics, investors and policymakers alike. Understandably, there exists a large literature (see Baumeister, ; Lux et al , ; Degiannakis and Filis, ,; Gupta and Wohar, for detailed reviews) aiming to predict oil price movements using various types of econometric methodologies (univariate and multivariate; linear and non‐linear), and predictors (macroeconomic, financial, behavioural, institutional).…”
Section: Introductionmentioning
confidence: 99%
“…Understandably, there exists a large JEL classification: C22, C32, Q41. literature (see Baumeister, 2014;Lux et al, 2016;Filis, 2017a,2017b;Gupta and Wohar, 2017 for detailed reviews) aiming to predict oil price movements using various types of econometric methodologies (univariate and multivariate; linear and non-linear), and predictors (macroeconomic, financial, behavioural, institutional).…”
Section: Introductionmentioning
confidence: 99%
“…Although the performance of many different statistically based historical risk models for the oil market has been deeply analyzed (e.g., Aloui & Mabrouk, 2010;Cabedo & Moya, 2003;Costello, Asem, & Gardner, 2008;Fan, Wei, & Xu, 2004;Fan, Zhang, Tsai, & Wei, 2008;Feng, Wu, & Jiang, 2004;Giot & Laurent, 2003;González-Pedraz, Moreno, & Peña, 2014;Lux, Segnon, & Gupta, 2016;Sadorsky, 2006;Youssef, Belkacem, & Mokni, 2015;and 1 It is well known that a time window that is too long makes today's value almost unconditional, and hence of almost no value, whereas one that is too short leads to statistically poor results and might leave out important past data. 2 It is worth noting that the square root extension is theoretically acceptable only in the presence of normal results.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the historical simulations used by, for example, Cabedo and Moya () have the opposite problem: They capture the empirical returns distribution but do not make it conditional on volatility. Third, more advanced parametric models mostly built within the family of generalized autoregressive conditional heteroskedasticity (GARCH) models improve fits (Aloui & Mabrouk, ; Chiu, Chuang, & Lai, ; Giot & Laurent, ; Hung, Lee, & Liu, ; Lux, Segnon, & Gupta, ; Youssef, Belkacem, & Mokni, ); however, they require fat‐tailed distributions, long memory, and other features that lead to heavy parameterization, making the approach less tractable.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers, therefore, study VaR using parametric approaches, in which the volatility in Equation (1) comes from a variety of GARCH models. Recent attempts include Youssef et al (2015), who combine long-memory GARCH models with extreme value theory; Lux et al (2016), in which Markov-switching multifractal and various GARCH models are applied to model and forecast oil price volatility; Chkili, Hammoudeh, and Nguyen (2014), in which a wide range of linear and nonlinear GARCH models are used to study the VaR of energy and precious metal commodities; and Giot and Laurent (2003), in which it is shown that skewed Student APARCH works best in forecasting VaR in commodity markets.…”
mentioning
confidence: 99%